Strategy and Policy for Strengthening the Agricultural Cooperative Business in East Java, Indonesia - Soetriono Soetriono; Djoko Soejono; Dimas B. Zahrosa; Ariq Dewi Maharani; Rita Hanafie (Publisher of Widyagama University of Malang (UWG Press), 2019)
The purpose of the study is to analyze business performance, financial resources, and strategies for developing agricultural cooperatives in East Java. The research approach used was a qualitative and quantitative descriptive approach. The research locations were in Malang regencies, Lumajang, Bojonegoro, Tulungagung, Madiun, Situbondo, Banyuwangi, and Sumenep. Secondary and primary data, including cooperative performance, SWOT, and financial data, were carried out to obtain a cooperative description. The analysis methods used were descriptive analysis, financial ratios, SWOT and FFA. The results showed that agricultural cooperatives showed a strong institutional position in supporting food sovereignty. The number of active cooperatives reached 27461 units with 7.62 million members. Cooperatives in healthy performance were found in Malang, Situbondo, Tulungagung and Madiun Regencies. The cooperative development should be emphasized on implementing functions of member annual meeting, developing innovation, making economic partnerships, strengthening capital formation, applying positive values of cooperatives to all members, facilitating members into the agribusiness chain, and improving the cluster of the production system. The strategies applied for East Java Cooperativesare prioritized on human resources, institutions and empowerment, facilities and infrastructure, and finance.JEL Classification: Q12, Q13, R58